PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF WORDWALL MATERI AKTIVITAS SENAM LANTAI PADA SISWA KELAS VI SDN PERCOBAAN 1 MALANG - Mario Azriel Iman Chodori; Siti Nurrochmah; Annang Widodo Raharja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media based on Wordwall application in order to increase the interest and motivation ofClass VI students in the material of gymnastics floor. The background of this study is the low motivation of students towards learning pjok theory which is still dominated by Lecture methods and the use of conventional media such as PowerPoint. Research using Research and Development (R & D) with ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The products developed are validated by media, material, and learning experts, and tested on students through small (12 students) and large (30 students) groups. Validation results show thatWordwall media is very valid with an average value above 90%. The trial also showed a significant increase in students ' interest in learning,especially in the aspect of attraction. In conclusion, Wordwall media is effective and feasible to be used as an alternative to PJOK learning that ismore interesting and interactive, especially in learning floor gymnastics.